Analisis Pengaruh Pengadaan Buku Teknologi Dalam Meningkatkan Literasi Mahasiswa Telkom University Purwokerto (Studi Kasus Perpustakaan TUP) - Dedy Tigor Manurung; Naura Soffin Fadhilah; Yulia Margareth Sirait (Department of Science and Technology Ibrahimy University, 2024)
This research assesses the influence of acquiring technology books on student literacy at Telkom University Purwokerto through the SCOR (Supply Chain Operations Reference) Model. The study seeks to evaluate the efficiency and effectiveness of supply chain processes Plan, Source, Make, Deliver, and Return while recognizing key performance indicators. The results indicate that the Return process has the greatest impact on overall performance, achieving a total score of 8.725 out of 18.52. Conversely, the Plan and Deliver processes exhibit slight contributions, recording scores of 0.015 and 0.01, respectively, signifying the necessity for enhanced demand planning and book distribution approaches. The research underscores a notable disparity in digital literacy, with the usage rate for e-books at just 0.013%, whereas printed books stand at 30.69%. This study aids in formulating strategic suggestions, such as improved demand projection, streamlined distribution networks, and the promotion of digital literacy via e-book initiatives. This research is distinct from earlier studies as it centers on the specific context of procuring technology books within a university environment and utilizes a systematic KPI-based assessment. Although it offers valuable insights, the research is constrained by its focus on just one institution and the sole application of the SCOR framework. It is suggested that future research incorporate wider datasets, examine other methodologies, and investigate new digital solutions. By tackling these issues, the results seek to enhance the position of university libraries as hubs of effective and inventive digital literacy.